The Impact of COVID-19 on Price Volatility of Crude Oil and Natural Gas Listed on Multi Commodity Exchange of India - Meher, Bharat Kumar; Hawaldar, Iqbal Thonse; Mohapatra, Latasha; Sarea, Adel M. (International Journal of Energy Economics and Policy, 2020)
The impact of COVID-19, due to the wide-spread demand and supply destruction and downward movement of crude oil prices is of concern for all those connected with the oil and gas industry. In this study, an attempt has been made to estimate the price volatility of crude oil and natural gas listed on Multi Commodity Exchange of India (MCX). We measured the leverage effect of COVID-19 on price volatility of crude oil and natural gas by using the daily prices of crude oil and natural gas from 1st May 2017 to 30th April 2020. The findings of the study reveal that there is a presence of leverage effect of COVID-19 on the price volatility of crude oil. However, this leverage effect is not present on the price volatility of natural gas. The findings of the study will help investors to develop investment strategies and to the policymakers to formulate appropriate policies to overcome or minimise the impact of COVID-19. The forecasting graphs of crude oil prices indicate that there is a possibility that price volatility will be higher in the future. However, it is difficult to forecast the expected price volatility of natural gas for the future because the price volatility graph is extremely fluctuating. Keywords: COVID-19, Asymmetric Volatility, Leverage Effect, Crude Oil, Natural Gas, MCX Limited. JEL Classifications: G15; G20; G21; G22; G23 DOI: https://doi.org/10.32479/ijeep.10047